A need for foreign-language policies at tourist destinations in South Africa : Case study: 'Cradle of humankind' World Heritage Site. - Turcato, Aurélien Roman (My University, 2008)
This study examines the availability of translated material into foreign languages, more specifically into French, at tourist destinations in South Africa. The Cradle of Humankind is chosen to carry out a case study and to show the lack of material available in languages other than English and the subsequent need for the development of a foreign-language policy. This study attempts to show the way forward by translating Maropeng’s miniguidebook into French based on a prior analysis of the original English text following Nord’s translation-relevant text analysis model. Furthermore, this study is not an end in itself but a step toward a better representation of official South African languages as an integral part of language policies throughout the country, as suggested by the Constitution.
Keywords: language policy; translation; tourism; Maropeng